Acute Kidney Injury Complicated Epstein-Barr Virus Infection in Infancy - Gamze Ozgurhan; Mustafa Ozcetin; Aysel Vehapoglu; Zeynep Karakaya; Fatih Aygun (Hindawi Limited, 2015)
Infectious mononucleosis is an acute lymphoproliferative disorder caused by the Epstein-Barr virus (EBV) and seen most commonly in children and young adults. Clinical presentation of the disease is characterized by fever, tonsillopharyngitis, lymphadenopathy, and hepatosplenomegaly, whereas serological findings of this benign disorder include positive heterophilic antibody formation (transient increase in heterophilic antibodies) and prominence of hematological lymphocytosis of more than 10% of atypical lymphocytes. An EBV infection is usually asymptomatic in childhood, but acute kidney injury can be a rare complication during its course. Most cases recover from the disease completely. Early recognition of EBV infection and estimation of its complication are important for its prognosis. In light of previous literature, we discuss the case evaluated as an EBV infection complicated by acute kidney injury in early childhood and results of tubulointerstitial nephritis shown on a renal biopsy that was later diagnosed as an EBV infection by serological examination.